The Influence of School Principal Leadership Style on Teacher Performance at SD Negeri 2 Banda Aceh: A Literature Review - Nurul Izzati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the influence of school principal leadership styles on teacher performance at SD Negeri 2 Banda Aceh, utilizing a literature review approach. The effective leadership of school principals is crucial in fostering a positive working environment and enhancing teacher motivation, which in turn impacts the overall academic performance of students. This literature review synthesizes existing research on various leadership styles, including transformational, transactional, and instructional leadership, and their respective effects on teacher engagement, job satisfaction, and professional development. The findings suggest that a supportive leadership style significantly contributes to improved teacher performance, while also highlighting the importance of context-specific leadership practices. The study concludes by discussing implications for educational policy and practice, emphasizing the need for effective training programs for school leaders.